Comparison of mental burden across different types of cancer patients in Nepal: a special focus on cervical cancer patients - Soumi Roy Chowdhury; Alok K. Bohara; Jeffrey Drope (College of Public Health Sciences, Chulalongkorn University, 2022)
Purpose - The purpose of the study is to assess the differential impact of gender and cancer sites on mental burden across different types of cancer and control patients. Design/methodology/approach - The paper is based on a primary survey undertaken in 2015-2016 of 600 cancer and 200 control patients across five hospitals of Nepal. The data was analyzed using propensity score matching methods and treatment effect weighting estimators. Findings - The authors find that of all the types of patients covered under this study, cervical cancer patients suffered from a greater intensity of anxiety and lack of functional wellbeing. On an average, all other female, male cancer patients, and control patients experience significantly lower intensity of mental burden in the range of 1.83, 2.63 and 3.31, respectively when compared to patients of cervical cancer. The results are robust across all the four treatment effect estimators and through all the measures of mental burden. The implications of suffering from cervical cancer, as a unique gynecological cancer was studied in-depth. An effect size analysis pointed out to the dysfunctional familial relationship as additional causes of concern for cervical cancer patients. Originality/value - An important finding that emerged is that female cancer patients especially those who have cervical cancer should be given special attention because they appear to be the most vulnerable group. Further work is needed to delineate the reasons behind a cervical cancer patient facing higher amount of stress.